The ROLE OF GREEN PRODUCT INNOVATION AS A MEDIATOR FOR GREEN CUSTOMER INTEGRATION ON ECONOMIC PERFORMANCE IN THE AGRO-FOOD AND BEVERAGE INDUSTRY IN JAMBI PROVINCE - Budaya, Indra; Lova, Anggil Novra; Sarmigi, Elex (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
This research aims to find out and explain how green customer integration on economic performance is mediated by green product innovation in agro-industry, both directly and indirectly. Background Problems: Green businesses refer to any business that adheres to environmental sustainability standards in its management, its efforts to use renewable resources, and its struggle to reduce the negative environmental impact of its actions in increasing its business income. Novelty: Green product innovation has an essential role in mediating the relationship between green customer integration and economic performance. Research Methods: This research is quantitative. The sampling method used was purposive sampling with a research instrument in the form of a questionnaire distributed to 240 respondents who were food and beverage agro-industry business actors in Jambi Province. Finding/Results: green customer integration has a direct effect on green product innovation and economic performance. Conclusion: These findings prove that Green Customer Integration determines economic performance. The better a company integrates environmentally friendly products with its consumers, it can increase environmentally friendly product innovation, which can influence economic performance or business profits.